Motor skills in the structure of motor readiness of karate athletes 9 years old (using the example of the «Yoko geri chudan» kick) - Svitlana Marchenko (Слобожанський науково-спортивний вісник)
Purpose of the study – to determine the place of motor skills in the structure of motor training of 9-year-old karate boys in the process of learning «Yoko geri chudan» side kick.